Renewable Energy Policy as Indonesia's Energy Security Strategy - Melaty Anggraini (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
Indonesia has the potential of abundant natural resources that made the country a global energy producer before, but because of the dwindling energy reserves owned makes the position reversed and caused Indonesia’s policy to have energy supply from other countries, besides the high utilization of fossil energy in Indonesia has much impact on environmental damage such as air and water pollution and does not support economic development patterns. Sustainable. For this reason, the Indonesian government needs to improve its policy regulations by focusing on the development and management of new renewable energy as a form of a national resilience strategy and environmental impact reduction. This new renewable energy will be analyzed from 4 dimensions of political considerations in constructivist theory, namely idiographic, purposive, ethics, and instrument, to see if it will be appropriate for Indonesia’s national energy security strategic plan. This research uses qualitative methods that explain the two variables involved in this new renewable energy and energy security and look for reasons for the need to include the concept of renewable energy in the national energy security policy strategy, with qualitative data collection techniques and library literature sources and interview results of related quotations. The results of the four-dimensional analysis will explain that the concept of renewable energy ideas is a social construction that can be a policy recommendation in the field of energy for the government to maintain the availability of energy supply in the strategic issue of national energy securityKeywords: Renewable Energy, Constructivist, Climate Change, Energy Security